2014
DOI: 10.1037/lhb0000077
|View full text |Cite
|
Sign up to set email alerts
|

Language style matching and police interrogation outcomes.

Abstract: This research examined the coordination of interrogator and suspects' verbal behavior in interrogations. Sixty-four police interrogations were examined at the aggregate and utterance level using a measure of verbal mimicry known as Language Style Matching. Analyses revealed an interaction between confession and the direction of language matching. Interrogations containing a confession were characterized by higher rates of the suspect matching the interrogators' language style than interrogations without a conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 54 publications
(84 reference statements)
1
36
1
1
Order By: Relevance
“…These LIWC categories, which are described in detail by Pennebaker et al . [45], have been widely used in applied psychology [17,46,47] and shown to provide reliable and valid analysis of written and spoken texts [48,49]. An account of LIWC's reliability and further examples of the words contained within each category are given in Pennebaker et al .…”
Section: Methodsmentioning
confidence: 99%
“…These LIWC categories, which are described in detail by Pennebaker et al . [45], have been widely used in applied psychology [17,46,47] and shown to provide reliable and valid analysis of written and spoken texts [48,49]. An account of LIWC's reliability and further examples of the words contained within each category are given in Pennebaker et al .…”
Section: Methodsmentioning
confidence: 99%
“…Like behavioral mimicry, linguistic mimicry is ubiquitous and serves as a strategic "social glue" (we like those we mimic, and mimic those we like; ) that can have positive or negative consequences across a range of human interactions (Babcock et al 2014;Lord et al 2015;Kulesza, Dolinski, Huisman and Majewski 2013;Ludwig et al 2013;O'Donnell et al 2015;Rains 2015;Richardson et al 2014;Yilmaz 2015). For example, higher levels of linguistic mimicry increase romantic interest between individuals who are speed-dating (Ireland et al 2011), increase preferences for products (Tanner et al 2008), and increase team performance, trust, and cohesion (Gonzales et.…”
Section: Behavioral and Linguistic Mimicrymentioning
confidence: 99%
“…Richardson et al. () demonstrated that alignment of linguistic styles between police interrogators and suspects was associated with higher confession rates. Ireland and Henderson () also observed that language style matching in the initial phases of negotiations predicted more positive interactions.…”
Section: Background: the Many Faces Of International Diplomatic Negotmentioning
confidence: 99%